Enkele teoretiese en metodologiese implikasies van die sisteembenadering in die Kommunikasiekunde - H.J. Groenewald; M. Pitout; L. Nieuwmeijer (Communicare)
A SYSTEMS approach to the phenomenon of communication implies in many important respects a break with the traditional assumptions and principles of communication theories and research methodologies. There is increasing dissatisfaction among communicologists with the influence of positivism (and respectively reductionism) in Communication Science as in the case of the covering law model. Some of the most important theoretical implications such as holism, selfregulation, hierargical organization, adaptation and organized complexity are briefly discussed. Attention is also given to methodological implications of concepts such as information, message. group, rules and meaning.